2020
DOI: 10.3390/land9120508
|View full text |Cite
|
Sign up to set email alerts
|

Being on Land and Sea in Troubled Times: Climate Change and Food Sovereignty in Nunavut

Abstract: Climate change driven food insecurity has emerged as a topic of special concern in the Canadian Arctic. Inuit communities in this region rely heavily on subsistence; however, access to traditional food sources may have been compromised due to climate change. Drawing from a total of 25 interviews among Inuit elders and experienced hunters from Cambridge Bay and Kugluktuk in Nunavut, Canada, this research examines how climate change is impacting food sovereignty and health. Our results show that reports of food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…Furthermore, whereas residents found technology is positive for enhancing capacity to adapt to change, many participants also emphasized the downsides of technologies, including the reduction in knowledge transfer due to the loss of youth interest in subsistence. These responses are similar to a study of communities in Nunavut where residents reported concerns that youth are more interested in jobs, money, and technology than subsistence, thereby threating transmission of traditional knowledge (Panikkar and Lemmond 2020). The generic capacity to address economic development in the three https://www.ecologyandsociety.org/vol26/iss4/art1/ communities were considered more important than the need to increase income, employment, improve education, and strengthen cultural identity.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, whereas residents found technology is positive for enhancing capacity to adapt to change, many participants also emphasized the downsides of technologies, including the reduction in knowledge transfer due to the loss of youth interest in subsistence. These responses are similar to a study of communities in Nunavut where residents reported concerns that youth are more interested in jobs, money, and technology than subsistence, thereby threating transmission of traditional knowledge (Panikkar and Lemmond 2020). The generic capacity to address economic development in the three https://www.ecologyandsociety.org/vol26/iss4/art1/ communities were considered more important than the need to increase income, employment, improve education, and strengthen cultural identity.…”
Section: Discussionsupporting
confidence: 71%
“…The concern about cultural continuity, intergenerational transfer of knowledge and skills and youth participation in subsistence activities is not unique to the three communities in our study. Time spent outdoors has been declining over the past decades (Louv 2008), including among Indigenous youth of the Canadian Arctic (Pearce et al 2011, Holen et al 2012, Tremblay 2018, Panikkar and Lemmond 2020. Participants in our study noted the diminishing capacity to respond to climate threats and environmental adversities by use of traditional ecological knowledge.…”
Section: Discussionmentioning
confidence: 70%
“…Inuit and Inupiat individuals from 11 studies perceived that the integrity of their connection to the land is essential for their mental health and resilience (Boulanger-Lapointe et al, 2019;Cunsolo Willox et al, 2012, 2013a, 2013bHarper et al, 2015;Ostapchuk et al, 2012;Petrasek MacDonald et al, 2013Sansoulet et al, 2020;Sawatzky et al, 2020;Wolsko & Marino, 2016). Eight of the studies found that for many Inuit, going outside the community (i.e., travelling or performing activities on the land) is an important way of dealing with the stress and problems of daily life (Boulanger-Lapointe et al, 2019;Bunce et al, 2016;Cunsolo Willox et al, 2012, 2013a, 2013bDurkalec et al, 2015;Panikkar & Lemmond, 2020;Petrasek MacDonald et al, 2015). In Nunatsiavut, Nunavik, and Nunavut, Inuit participants of 10 studies reported feeling more relaxed, calm, and peaceful, as well as healthier and happier, when on the land (Boulanger-Lapointe et al, 2019;Bunce et al, 2016;Cunsolo Willox et al, 2012, 2013a, 2013bDurkalec et al, 2015;Harper et al, 2015;Middleton et al, 2020a;Petrasek MacDonald et al, 2015;Sawatzky et al, 2020).…”
Section: Study Selectionmentioning
confidence: 99%
“…Writing of his experience on a mission to Canada, former Special Rapporteur on the Right to Food, Olivier de Schutter, highlighted the impacts and consequences on food security from climate change in relation to Indigenous communities and access to traditional food systems [28]. Nearly 10 years later, communities across Canada-part of the area known to many Indigenous nations as Turtle Island, which encompasses the region of North America [29]-continue to struggle with the growing and potential effects of climate change [30], as well as the impacts of settler economic systems, environmental disruption, and other pressures, on accessing traditional foods [31].…”
Section: The Race To Zero: Ailing Food Governance In a Globalized Eco...mentioning
confidence: 99%